GOVERNMENT SCIENCE PARADIGM: INNOVATION IN REGIONAL GOVERNMENT ADMINISTRATION - Ayu Dewi Mayasari; Dama, Melati; Hartutiningsih (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
The paradigm of regional government administration has undergone changes with innovations in the government system. The goal of this innovation is to raise regional government administration's effectiveness. Regional governments have the freedom to innovate in the administration of regional government without having to worry about legal issues, as long as the innovation does not cause negative impacts and remains in accordance with the applicable government administration mechanisms. Innovation in regional government administration includes various forms of reform carried out to improve performance and public services at the regional level. The scope of this innovation includes improving public services, community participation and empowerment in addition to boosting regional competitiveness. Innovation in government can also be viewed from the standpoint of government function is carried out in 3 ways, namely service innovation, development innovation and community empowerment innovation. The concept of innovation, which is then outlined in a policy, is considered to have provided sufficient space for regional governments to implement several reforms in each regional government administration to enable the implementation of good governance procedures.